Highway materials a guide book for beginners - Ratnasamy Muniandy (Penerbit Universiti Putra Malaysia, 2001)
This book is intended for practising maintenance engineers, contracting engineers, consultants and engineering students who need a clear reference to help them select the materials and/or treatments that are appropriate for use on specific sites. Considerable effort has been put into describing the equipment and explaining the testing procedures for the various tests involved in roadworks.